Identification and management of key influencing factors in China’s pig supply chain from the perspective of resilience and sustainability synergy - Wendi Wang; Shanshan Wang; Dongshi Sun; Yadan Zhao (Frontiers in Sustainable Food Systems)
Based on this version, we have updated the Abstract as follows: The pig supply chain (PSC) is influenced by the pig cycle, environmental regulations, and livestock health and safety incidents, making its supply chain management highly complex. Currently, the primary focus of PSC management is on resilience upgrading, with less emphasis on sustainable development, which, limits the growth of PSC. Taking China, the world’s largest pig producer and consumer, as an example, this paper constructs an influencing indicator system for PSC from the perspective of resilience and sustainability synergy (RSS). It applies Fuzzy DEMATEL to calculate the causal relationships between indicators, ANP to calculate indicator weights, and obtains a comprehensive ranking and identifies key influencing factors (KIFs). Moreover, this paper analyzes the relationships and constraints between influencing factors. The stability of the KIFs and the regional applicability of the indicator system were verified through the fuzzy comprehensive evaluation of RSS in PSC in Zhejiang Province (eastern China), Henan Province (central China), and Sichuan Province (western China). The results show that Enterprise organizational capability (F2), Supply chain environmental interaction across the lifecycle (F13), Trust relationships among entities (F19), Logistics network adaptability (F7), Learning and continuous improvement mechanisms (F12), Supply chain digitalization level (F4), and Technological innovation capability (F8) are key factors influencing RSS in PSC. The findings emphasize that China’s PSC should prioritize resilience while leveraging the synergistic effects of KIFs to achieve sustainable development. This paper provides practical optimization strategies from the perspective of RSS for overcoming challenges related to environmental interactions and redundant configurations in PSC management.